Epidemiology and Burden of Chronic Constipation - Maria Ines Pinto Sanchez; Premysl Bercik (Canadian Journal of Gastroenterology)
Chronic constipation is an important component of clinical gastroenterology practice worldwide. Based on the definition, either self-reported or using Rome criteria, chronic constipation can affect from 2% to 27% of the population. Constipation is physically and mentally troublesome for many patients, and can significantly interfere with their daily living and well-being. Although only a proportion of patients with constipation seek medical care, most of them use prescribed or over-the-counter medication to improve their condition. The health care costs of constipation are significant as evidenced by the hundreds of million dollars spent yearly on laxatives alone. Because constipation is more common in older patients and life expectancy is increasing, an increase in the prevalence of constipation is expected in the years to come, with the associated impact on quality of life and socioeconomic burden.